De la mesure au sens de la mesure - Pierre-Marie David (Revue d'anthropologie des connaissances)
To give the measure a meaning, it should be reported to a system of values, which permits evaluation and judgment. This is the theoretical bias that underlies this article on writing practices in the fight against AIDS from an approach at the intersection of the political anthropology of health and science studies. To investigate the pathways and potential bottlenecks between the measure and its meaning, I describe the history of the development of indicator systems to support AIDS treatment in the Central African Republic (CAR), a country among the poorest in the world and with very low state capacity. The article specifically aims to describe and understand how, in this context of great material uncertainty and structural violence, a measurement system in the fight against AIDS is constructed and secondly how the measures have been reported at the intersection of global and local; framing what I call a scriptural economy. At first I present the development of practices, knowledge and tools for measurement of HIV infection in the CAR. Secondly I address the unintended effects of the uses of measurement.